Current status and management of pancreatic trauma with main pancreatic duct injury: A multicenter nationwide survey in Japan. (19th January 2021) - Ando, Yasuhisa; Okano, Keiichi; Yasumatsu, Hiroshi; Okada, Toshimasa; Mizunuma, Kimiyoshi; Takada, Minoru; Kobayashi, Shinjiro; Suzuki, Keisuke; Kitamura, Nobuya; Oshima, Minoru; Suto, Hironobu; Nobuyuki, Miyatake; et al.
Abstract: Background: Pancreatic trauma is reportedly associated with high morbidity and mortality. Main pancreatic duct (MPD) injury is critical for treatment. Methods: As a study project of the Japanese Society for Abdominal Emergency Medicine (JSAEM), we collected the data of 163 patients with pancreatic trauma who were diagnosed and treated at JSAEM board‐certified hospitals from 2006 to 2016. Clinical backgrounds, diagnostic approaches, management strategies, and outcomes were evaluated. Results: Sixty‐four patients (39%) were diagnosed as having pancreatic trauma with MPD injury that resulted in 3% mortality. Blunt trauma and isolated pancreatic injury were independent factors predicting MPD injury. Nine of 11 patients with MPD injury who were initially treated nonoperatively had serious clinical sequelae and five (45%) required surgery as a secondary treatment. Among all cases, the detectability of MPD injury of endoscopic retrograde pancreatography (ERP) was superior to that of other imaging modalities (CT or MRI), with higher sensitivity and specificity (sensitivity = 0.96; specificity = 1.0). Conclusions: Acceptable outcomes were observed in pancreatic trauma patients with MPD injury. Nonoperative management should be carefully selected for MPD injury. ERP is recommended to be performed in patients with suspected MPD injury and stable hemodynamics. Abstract : Highlight Ando and colleagues analyzed data from 163 patients with pancreatic trauma in a nationwide multicenter study. They found that serum amylase and C‐reactive protein levels were significantly higher in patients with main pancreatic duct injuries, indicating that endoscopic retrograde pancreatography was the most accurate imaging modality for assessing pancreatic duct injury.